A Laboratory Approach Considering Salinity to Investigate Archie's Parameters in Deep Shale: A Case Study in Longmaxi Formation, Southern Sichuan. (10th March 2022) - Li, Yanran; Liu, Xiangui; Cai, Changhong; Hu, Zhiming; Wu, Bo; Mu, Ying; Duan, Xianggang; Zhang, Qingxiu; Zeng, Shuti; Guo, Jingshu; Pu, Zhijin
Abstract : Archie's parameters are substantial to be investigated in the evaluation of water saturation. Many researchers adhered to the opinion that Archie's equation can still be applied to water saturation calculation in shale if the accuracy of relative parameters could be improved. External conditions, such as temperature, confining pressure, water salinity, wettability, and displacement, may influence the determination of Archie's parameters. The aim of the study is to investigate the effect of salinity on Archie's parameters and their correlation with mineral composition and pore structure. The mineral contents and petrophysical properties were firstly acquired through X-ray diffraction (XRD) and basic measurements. Rock-electric experiments under different salinity were conducted on deep shale samples taken from Longmaxi (LMX) Formation in Luzhou (LZ). The results indicate that Archie's parameters of "a, " "b, " "m, " and "n " under actual brine salinity are assigned to 1.47, 1, 1.26, and 1.6, respectively. Our cementation factor is lower than that in other studies including (shaly) sandstones, carbonates, and shales, probably due to the extremely low porosity in study area. Salinity has a positive effect on cementation factor (m ) and saturation exponent (n ), suggesting the traditional assignment to Archie's parameters is inappropriate. It was concluded that the complicated pore structure and high porosity mainly associated with clay mineral may trigger the increased cementation factor. Further mathematical derivations confirmed that the rock resistivity is inextricable from pore system and establish a physical model. The paper provides a solid evidence base for further understanding and evaluation of water saturation in unconventional shale reservoirs, more significantly, innovatively unveils the research into Archie formula in deep shale reservoirs of southern Sichuan basin.